Optical implementation of visible gray-image morphology with the visual-area-coding technique - Konishi, T; Taniguchi, S; Tanida, J; Ichioka, Y (Applied optics (2004), 1996)
We present a novel scheme of visible gray-image morphology with the visual-area-coding technique (VACT). The VACT is a technique of digitized analog-optical computing in which data are converted into visible coded patterns and processed with the visible form. Because the achievable operations in the VACT are identical to those of mathematical morphology, mathematical morphology is adapted to gray-image morphology with the VACT. Computer simulation and optical experiments of the several operations in mathematical morphology verify the correctness of the proposed technique. The processing capacity of the proposed method is estimated in terms of the space-bandwidth product.